2004
DOI: 10.1080/09593332508618452
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Organism Re-Growth in Wastewater Disinfected by UV Radiation and Ozone: A Micro-Biological Study

Abstract: A series of disinfection experiments using UV radiation and ozone was performed on the secondary effluent from a wastewater treatment plant at a pilot plant scale. The microbial population in the inflowing wastewater and the treated outflow water were quantified for each of the treatment modules (fecal coliforms, fecal streptococci, Salmonella spp. (presence/absence), Clostridium Sulphite-reducers, Pseudomonas aeruginosa, Staphylococcus aureus, coliphages, nematodes, intestinal nematodes and pathogenic fungi).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Dungeni et al (2010) suggested UV disinfection as an additional treatment process of effluents to increase the effective inactivation and removal of pathogenic bacteria and viruses. However, Alonso et al (2004) found that Clostridium spp., showed a greatest degree of resistance to UV treatment. Munir et al (2010) indicated that the disinfection of effluents by UV process did not contribute to the significant reduction of antibiotic-resistant bacteria.…”
Section: Uv Irradiationmentioning
confidence: 95%
See 1 more Smart Citation
“…Dungeni et al (2010) suggested UV disinfection as an additional treatment process of effluents to increase the effective inactivation and removal of pathogenic bacteria and viruses. However, Alonso et al (2004) found that Clostridium spp., showed a greatest degree of resistance to UV treatment. Munir et al (2010) indicated that the disinfection of effluents by UV process did not contribute to the significant reduction of antibiotic-resistant bacteria.…”
Section: Uv Irradiationmentioning
confidence: 95%
“…Lepeuple et al (2004) reported that the C. perfringens is common in raw sludge and resistant to heat, and hence their removal can be related to removal of spore-forming species such as Bacillus sp. C. perfringens has been reported as resistant to oxidizing agents and to UV disinfection (Alonso et al 2004). Rouch et al (2011) indicated that C. perfringens appeared to be a conservative indicator during their study on the air drying of sludge generated from two STPs in Victoria, Australia.…”
Section: Clostridium Perfringensmentioning
confidence: 99%
“…Ozone was more effective than UV for the more resistant species. Clostridium sulfite-reducers and Pseudomonas aeruginosa exhibited significant regrowth over time, which was believed to be due to the presence of nutrients in the water (Alonso et al, 2004).…”
Section: Distribution Systems/regrowth and Biofilmmentioning
confidence: 99%
“…Therefore, posttreatment of anaerobically treated wastewater is usually required in order to improve the quality of effluent in accordance with the irrigation standards. This has been successfully done by conventional systems such as maturation ponds, waste stabilization ponds, polishing ponds, constructed wetlands, rotating biological contactors, moving bed biofilm reactor, downflow hanging sponge [60][61][62], and advanced oxidative processes (AOPs) [63,64].…”
Section: Posttreatment Requirementsmentioning
confidence: 99%